(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The use of "influencer marketing" to promote one's practice has gained popularity, and many healthcare practitioners have embraced this trend, including dental professionals. Promoting awareness on social media channels may result in an increase in referral numbers. Many dentists and dental offices are growing and becoming more successful by utilizing social media channels, particularly Instagram and Instagram influencers. People may consider a dentist a trusted source after seeing reviews or before and after photos shared by an influencer they trust and admire. Influencer marketing is a great marketing tool provided it is used under the umbrella of bioethics.